Influência do processo de usinagem na resistência à fadiga de laminados unidirecionais de epóxi/fibra de carbono - Cervini, Alex Ricardo (Universidade Federal de São Carlos, 2000)
Carbon fiber-reinforced polymer matrix composites exhibit a high strength-to-weight ratio, standing out for their excellent mechanical properties and widespread application in structurally demanding sectors such as the aerospace industry. Although these materials are often manufactured close to the final geometry of the component, machining operations are still required to achieve adequate dimensional and surface finishing. However, such processes may introduce structural damage capable of compromising the mechanical performance of carbon/epoxy composites. In this work, the influence of form-profile machining on the mechanical behavior of carbon/epoxy composites reinforced with continuous unidirectional fibers was investigated. It was observed that the surface integrity of the specimens was affected by the machining process, resulting in defects such as fiber cutting and exposure of free fiber ends without effective load transfer capability in the machined regions. The experimental evaluation focused on the fatigue behavior analysis of specimens machined transversely to the fiber orientation, with fatigue strength being the main investigated property. The analyzed material consisted of a carbon/epoxy composite manufactured with approximately 60% volume fraction of continuous unidirectional fibers. Fatigue tests were performed using the rotating bending technique with testing equipment developed by Tatnall Krouse. Surface integrity proved to be a determining factor in the fatigue performance of the material.
Influence of machining processes on the fatigue strength of unidirectional carbon fiber/epoxy laminates
Keywords: Compósitos; Fibra de carbono; Fadiga; Flexão rotativa; Rotating bending; Fatigue; Carbon fiber; Composites; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; 9. Indústria, Inovação e Infraestrutura